EB (epidermolysis bullosa)‐House Austria: Pioneering work for the care of patients with rare diseases. (10th August 2020) - Prodinger, Christine; Laimer, Martin; Bauer, Johann W.; Hintner, Helmut
Summary: The care of patients with epidermolysis bullosa (EB) poses a major challenge due to the rarity, heterogeneity and complexity of the disease as well as the occurrence of numerous primary and secondary extracutaneous manifestations, causing a significant morbidity and mortality. Specialized treatment centers are essential for offering these patients adequate care, including individual, interdisciplinary coordinated treatments according to current medical standards, and access to innovative therapeutic options. Against this background, the EB House Austria was founded in 2005 and designated the first national center of expertise for genodermatoses with a focus on EB in 2017. In the same year, it became a member of the European Reference Network for Rare Skin Diseases (ERN Skin). The pillars of this institution (outpatient clinic, research unit, academy, clinical study center) interact closely with each other, with numerous national and international clinical and scientific partners, as well as with patients and their relatives via the DEBRA Austria patient group. The development of the EB House Austria as a reference center is characterized by a long‐term pioneering work, which in turn could pave the way for the optimization of care for comparable diseases as well as general care structures.